Preeclampsia Screening Using BMI MAP and ROT Indicators: Skrining Preeklampsia Menggunakan Indikator BMI MAP dan ROT - Hasna Rosyidah; Rafhani Rosyidah (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Preeclampsia remains a major contributor to maternal morbidity and mortality worldwide. Specific Background Early detection strategies using clinical indicators such as Body Mass Index (BMI), Mean Arterial Pressure (MAP), and Roll Over Test (ROT) have been widely discussed in maternal health research. Knowledge Gap However, integrated assessment of these indicators in identifying preeclampsia risk is still limited in specific clinical settings. Aims This study aims to examine the role of BMI, MAP, and ROT in early screening of preeclampsia among pregnant women. Results The findings show that variations in BMI, MAP, and ROT measurements are associated with differences in preeclampsia risk classification. Novelty This study provides a combined perspective of three clinical indicators in preeclampsia screening. Implications The results highlight the importance of utilizing simple clinical measurements as part of early detection strategies in maternal healthcare services. Keywords: Preeclampsia, Body Mass Index,Mean Arterial Pressure, Roll Over Test, Maternal Health Key Findings Highlights Combined indicators identify varying risk categories Clinical measurements support early screening decisions Observed patterns assist risk classification in pregnancy